2019
DOI: 10.1111/1749-4877.12299
|View full text |Cite
|
Sign up to set email alerts
|

Inference by exclusion in the red‐tailed black cockatoo (Calyptorhynchus banksii)

Abstract: Inference by exclusion is the ability to select a given option by excluding the others. When designed appropriately, tests of this ability can reveal choices that cannot be explained by associative processes. Over the past decade, exclusion reasoning has been explored in several non-human taxonomic groups including birds, mainly in Corvids and Parrots. To increase our understanding of the taxonomic distribution of exclusion reasoning and therefore its evolution, we investigated exclusion performances in Red-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Similarly to other avian species (e.g., African grey parrots, Mikolasch et al 2011, Pepperberg et al 2013carrion crows, Mikolasch et al 2012;Clark's nutcrackers, Tornick and Gibson 2013;Eurasian jays, Shaw et al 2013;jackdaws, Schloegl et al 2011;keas, Schloegl et al 2009;ravens, Schloegl et al 2009; red-tailed black cockatoos, Subias et al 2019), skuas chose significantly more the rewarded cup over the unrewarded one in the full information condition (success probability Ps = 0.72 [95% IC: 0.64 -0.80]). Our results indicate that this species was able to rely on direct visual information for solving the task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to other avian species (e.g., African grey parrots, Mikolasch et al 2011, Pepperberg et al 2013carrion crows, Mikolasch et al 2012;Clark's nutcrackers, Tornick and Gibson 2013;Eurasian jays, Shaw et al 2013;jackdaws, Schloegl et al 2011;keas, Schloegl et al 2009;ravens, Schloegl et al 2009; red-tailed black cockatoos, Subias et al 2019), skuas chose significantly more the rewarded cup over the unrewarded one in the full information condition (success probability Ps = 0.72 [95% IC: 0.64 -0.80]). Our results indicate that this species was able to rely on direct visual information for solving the task.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of nonhuman animals to choose via exclusion has recently received considerable interest (e.g. Paxton et al 2018;Nawroth et al 2014;Petit et al 2015;Subias et al 2019). This cognitive mechanism, which refers to 'the ability to understand that if there are only two possibilities and if it is not A, it must be B' (O'Hara et al 2016), is typically explored through the use of a two-way object-choice paradigm i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where two cups are used, for example, they must reason that if the reward is not hidden in the cup shown to be empty, then it must be in the other one. Several species of corvids ( Schloegl et al, 2009 ; Mikolasch et al, 2012 ; Shaw et al, 2013 ; Jelbert et al, 2015 ), parrots ( Schloegl et al, 2009 ; Mikolasch et al, 2011 ; Pepperberg et al, 2013 ; O’Hara et al, 2015 , 2016 ; Bastos and Taylor, 2019 ; Subias et al, 2019 ), and apes ( Call, 2004 , 2006 ; Hill et al, 2011 ) readily reason in this way. The ability to reason by exclusion is present in some New World monkeys ( Sabbatini and Visalberghi, 2008 ; Marsh et al, 2015 ; Takahashi et al, 2015 ).…”
Section: Differences In Intelligence Across Speciesmentioning
confidence: 99%
“…On the other hand, during the OD test, piglets were presented with the CS+ object along with a novel object. To face situations where only part of the information about a problem is accessible, several studies [32][33][34][35][36][37] have shown that animals are able to use inference by exclusion (IE). IE refers to the ability to choose one option based on the systematic exclusion of alternatives [32].…”
Section: Discriminationmentioning
confidence: 99%